Persepsi Pengunjung Terhadap Desain Kawasan Wisata Pantai Pohon Cinta Di Gorontalo - Karim, Febriyanti (JARI: Journal of Architecture, Research and Innovation, 2024)
The perception of visitors to the tourist attraction of the Tree of Love Beach in Gorontalo is a study conducted with the aim of knowing the perception of visitors to the tourist attraction of the Love Tree in Marisa District, Pohuwato Regency, Gorontalo Province. The selection of the research location was carried out purposively, the study was conducted in October 2020, in this study the data collection methods used were direct field observation, questionnaire / interview distribution, documentation, and literature study. Analysis of research data using qualitative methods to answer research objectives based on information obtained from field observations. From the research results, it can be seen that the perception of visitors regarding the attractiveness of the love tree beach tourist attraction gives an attractive assessment with a percentage of 80%. The perception of visitors to the facilities / amenities with a good percentage of 46.67%, food and drink service is quite good with a percentage of 56.67%, beach security / safety is not guaranteed 48.33, beach cleanliness is not good 51.67%, additional facilities need to be done 100 %, satisfaction in making a visit is 50%, and visitor perceptions of accessibility to the Love Tree tourism object are considered good 86.67% and the mode of transportation on the object is smooth 48.33%